Manual for emerging architects - Forlati, Silvia; Isopp, Anne (Birkäuser, 2019)
During the first five years of a new architectural practice, typical problems arise that have to be managed. Based on the reports of young architectural practices, which were gathered in workshops throughout Europe, this manual analyzes commonly observed and frequent issues, and offers approaches to resolving them. What is special: the approaches were developed from daily working experience, and can be realistically implemented, not least because they are aimed at the different phases of a developing practice - "Getting started", "Making mistakes", "Going public", "Choosing a specialization", and "Doing competitions". For the second edition the texts were extended and corrected; statistics and charts were brought up to date. The cool presentation remains as appealing as in the first issue.